(untitled) (Journal of Medical & Health Sciences Review, 2025)
ABSTRACT Background: Stroke is a leading cause of long-term disability worldwide, often resulting in significantly reduced physical activity levels (PAL) among survivors. Active physiotherapy interventions are key to improving functional outcomes, but the sustainability of these gains is frequently compromised. Recent advancements in technology—such as wearable trackers, mobile applications, and tele-rehabilitation—have introduced new opportunities to enhance and monitor physical activity in real time. Objective: To evaluate the impact of active physiotherapy combined with technology-based monitoring on physical activity levels in stroke survivors, compared to usual care or less active interventions. Methods: A comprehensive search of six databases (PubMed, Embase, Cochrane CENTRAL, CINAHL, PEDro, Web of Science) was conducted up to March 2025. Randomized controlled trials (RCTs) and quasi-RCTs evaluating active physiotherapy with integrated technology (e.g., wearables, tele-rehab, mobile health apps) were included. The primary outcome was PAL, assessed using objective (e.g., accelerometers) or subjective (e.g., questionnaires) tools. Meta-analysis was conducted using a random-effects model. Risk of bias was assessed using the Cochrane RoB 2.0 tool, and certainty of evidence was evaluated via GRADE. Results: Seventeen studies (n = 2,134 participants) met inclusion criteria. The meta-analysis showed a significant improvement in PAL favoring the intervention group (SMD = 0.48, 95% CI: 0.30– 0.66, p < 0.001). Subgroup analyses revealed stronger effects in chronic stroke survivors and with wearable-based objective assessments. Heterogeneity was moderate (I² = 59%), and the overall certainty of evidence was rated as moderate. Conclusion: Active physiotherapy interventions supported by technology-based monitoring significantly enhance physical activity levels post-stroke. These findings support the integration of digital tools into stroke rehabilitation programs to promote sustained recovery and functional independence. Future research should prioritize long-term follow-up, comparative technology evaluations, and implementation strategies in diverse healthcare settings.